Advances in the Use of Metformin for Liver Disease - Bao, Jiaqi; Zhao, Yudi; Xu, Xiao; Ling, Sunbin (Current Medicinal Chemistry, 2025)
Metformin is a first-line drug for the treatment of type 2 diabetes with a good safety profile and relatively low cost. In recent years, many other effects of metformin have been discovered. In this review, we provide the research advances in metformin in liver disease. High-dose metformin can activate AMPK by inhibiting mitochondrial complex 1. In addition, low-dose metformin could activate lysosomal AMPK through PEN2. Activated AMPK can reduce fatty acid synthesis, inhibit tumor proliferation and metastasis, and reshape the tumor microenvironment. In addition, metformin can reduce ROS production by inhibiting mitochondrial complex 1, which can reduce liver damage. Therefore, metformin has been found to alleviate nonalcoholic fatty liver disease and cirrhosis, relieve liver damage, and reduce the incidence of hepatocellular carcinoma and cholangiocarcinoma. This information suggests that metformin may represent a new possibility for the prevention and treatment of liver diseases.
Keywords: Metformin